Content validation of the Patient-Reported Hamilton Inventory for Complex Regional Pain Syndrome: Validité de contenu du Hamilton Inventory for Complex Regional Pain Syndrome, une mesure des résultats déclarés par le patient. (April 2018) - Packham, Tara L.; MacDermid, Joy C.; Michlovitz, Susan L.; Buckley, Norman
Background: Complex regional pain syndrome (CRPS) is a perplexing neurological condition, and persons with CRPS experience substantial loss of daily roles and activities. A condition-specific measure is being developed to evaluate CRPS. Purpose: We describe the use of cognitive interviews to examine content validity of this patient-reported outcome measure for CRPS. Method: Interviews with 44 persons with CRPS were analyzed to identify problems with wording and support content validation. Item-total correlations were calculated for proposed subscales, and scores were plotted to consider floor/ceiling effects. Findings: Interviews identified questions where respondents considered factors unrelated to the construct of interest or were underaddressed by the questionnaire, including depression and skin temperature. The symptoms, daily function, and coping/social impact scales demonstrated satisfactory correlations (Cronbach's alpha 0.76–0.86). Despite a sampling bias of severity, no frank floor/ceiling effects were noted. Implications: This study builds a foundation for continuing development and evaluation of the measurement properties of the Patient-Reported Hamilton Inventory for CRPS. It makes explicit the iterative decisions involved in rigorous instrument development.